1998
DOI: 10.1002/(sici)1521-3803(199808)42:03/04<213::aid-food213>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Some physico-chemical properties and structural changes of bovine β-casein upon glycation

Abstract: The studies on casein structure modification contribute to better understanding of the role of nonamino acid components in forming casein complexes and improving ways of protein functionality. The objective of the experiments was to explain the influence of bovine milk casein glycation on some physico-chemical properties and structural changes. From the the analysis of glycation rate curve the reaction of the first order range can be assumed during the first 24 h, turning to a mixed type afterwards. The isoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…In below-presented studies we used analytical approach described by Nessar and Furth [19], that have been employed viz optical spectroscopy. It was found via that method, that seven glucose molecules were bound to one molecule of b-casein [14]. More recently, mass spectrometry has been employed in this field.…”
Section: Characterization Of Glycosylated B-caseinmentioning
confidence: 82%
See 2 more Smart Citations
“…In below-presented studies we used analytical approach described by Nessar and Furth [19], that have been employed viz optical spectroscopy. It was found via that method, that seven glucose molecules were bound to one molecule of b-casein [14]. More recently, mass spectrometry has been employed in this field.…”
Section: Characterization Of Glycosylated B-caseinmentioning
confidence: 82%
“…In our ealier studies we reported about the changes of bovine b-casein upon 15-day glycosylation with glucose [14]. We concluded that glycosylation of b-casein proceeded in stages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After these modifications, they concluded that glycation (1) shifted the pHi of casein toward more acidic pH values and (2) decreased the solubility at acid pH. In another publication, the same team (Darewicz et al 1999b) reported structural changes deduced by modification of absorption spectra in UV and a better heat stability of β-casein after its glycation. Corzo-Martinez et al (2010) worked on the characterization and improvement of rheological properties of glycated sodium caseinate with galactose, lactose, and dextran.…”
Section: Reaction With Sugarsmentioning
confidence: 97%
“…There are some reports in which the glycosylation enhances the thermal stability of food proteins [2,6,16,26,42], and the same functional improvement was also observed in fish Mf [7,19]. Figure 30.4 shows the thermal stability of carp Mf conjugated with alginate oligosaccharide (Mf-AO conjugate) under different NaCl concentrations and pH levels [34].…”
Section: Improvement Of the Thermal Stability And Emulsion-forming Abmentioning
confidence: 99%